Penerapan E-CRM pada Usaha Salon dalam Meningkatkan Loyalitas dan Pelayanan terhadap Pelanggan - Nur’Ahya Anisa; Yuliazmi Yuliazmi; Grace Gata (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
D'Moze Salon is a company engaged in the sale of salon services established in 2009 with its first branch located in Tanjung Duren, West Jakarta. Some of the factors faced by D 'Moze Salon are handling verbally delivered complaints, a large number of customers visit make a long waiting list for treatment, and it is difficult to identify and retain loyal customers. Implementing CRM is one way for companies to be able to create good relationships with customers and mutual benefits. Along with the development of information technology requires companies to apply technology in business because business competition is increasingly high. By applying the Electonic Customer Relationship Management (E-CRM) model that provides a means of interface for customers that can help solve existing problems so that they can benefit both customers and the company. The interface provided is a web-based E-CRM system created with the PHP programming language and MySQL database. Using this E-CRM system D'Moze Salon is easier to manage the provision of services so the level of customer satisfaction increases also their loyalty. Thus, complaints will be reduced, testimonials from satisfied customers are increasing. This will capture potential new customers to choose D’Moze as the salon for treatment.